"The extent of science teachers' awareness of the theory of multiple intelligences and its relationship with the deductive thinking of their students" (Journal of the College of Basic Education, 2024)
The current research aims to investigate science teachers' awareness regarding the theory of multiple intelligences and its relationship with the deductive thinking of students. To achieve the current research objective, the researcher followed a descriptive-correlational approach. The research community was identified as the teachers and fifth-grade students in the second educational directorate of Al-Karkh, while the current research sample was defined as 114 male and female teachers and 2005 male and female students from the fifth grade . The researcher prepared research tools for the current study, including a multiple intelligences questionnaire and a deductive thinking scale. The researcher extracted psychometric characteristics from these tools, including validity and reliability. After ensuring the psychometric properties and applying the research tools to the study sample, the current study arrived at the following results: 1- The level of awareness of teachers about the theory of multiple intelligences is above average.2- Differences in the average deductive thinking in the dimensions of data analysis, building scenarios, making judgments, drawing conclusions, and hypothetical average function, indicating that data analysis, building scenarios, making judgments, and drawing conclusions are above average